Financial Sustainability and Corporate Social Responsibility Under Mediating Effect of Operational Self-Sustainability - Hussain, Rai Imtiaz; Bashir, Shahid; Hussain, Shahbaz (Frontiers in Psychology, 2020)
Operational and financial sustainability remained issues for the microfinance industry over time. The microfinance industry is struggling to gain self-sufficiency in Pakistan due to non-performing loans and operational costs. At the same time, deliberation on corporate social responsibility (CSR) is also getting consideration both in academic literature and organizational practices. However, studies on CSR and financial performance in the microfinance sector are scarce especially in Pakistan. CSR will develop customer attraction and loyalty, employee attraction, motivation and loyalty, MFIs’ reputation and access to capital and eventually build in financial performance. Interviews were conducted with branch managers of microfinance institutions to test the previous questionnaires. A self-administered survey was conducted to collect data from the managers of the microfinance banks operating in Punjab. Descriptive and inferential statistics were performed to answer research questions using Smart PLS. Most of the microfinance institutions believe in social responsibilities but lacks fund allocation and approval from higher management and results are in line with prior studies. These empirical findings lead to the perception that CSR is not a barrier for microfinance banks to perform as they have access to capital. The results indicated a strong positive correlation between CSR and financial performance of the MFIs. CSR also found a positive correlation with customer retention, employees' motivation and attraction and business reputation. CSR was correlated with access to capital but was found weak. The research also narrated the limitation and practical implications of the study. The study also discussed further research directions.